Retrospective study on the accuracy of the cone beam computed tomography technique in detecting the mesiopalatal canal in upper second molars (Acta Scientiarum. Health Sciences, 2025)
Knowing the anatomy and morphology of the maxillary molar canals and the location of the MV2 are extremely important for endodontist clinics. This study evaluated the morphology of the maxillary second molar and the incidence of the Mesiopalatal canal using cone beam computed tomography. Retrospective secondary data were collected from patients of a reference radiology clinic in Maringá, state of Paraná, undergoing imaging exams in a Prexion 3D scanner. Images were analyzed in the axial, sagittal, and coronal sections. When MV2 was identified, it was categorized according to the Vertucci’s Classification. Descriptive analysis was performed for age, gender, the morphology of the maxillary second molar, the presence of the second buccal canal, and classification according to its morphology. A total of 173 patients were analyzed, and 230 maxillary second molars were found, with the presence of the Mesiopalatal in 29.1%. The type IV Vertucci classification was the most frequent (40.3%). The study concluded that there is an expressive occurrence of the second buccal canal in 29.1% of cases, and the most recurrent morphology is type IV, according to Vertucci’s classification.